Proactive and Sustainable Transport Investment Strategies to Balance the Variance of Land Use and House Prices: A Korean Case - Cho, Seongkyun; Choi, Keechoo; Yi, Yongju (Sustainability (Switzerland), 2022)
The transport infrastructure sustaining the ascension of land values while synergizing with the industries is a condition optimized for economic sustainability. In general, although transport investment aims to create a more reliable, less congested, better-connected transport network, the secondary aim is to facilitate balanced and sustainable development by enhancing accessibility to infrastructures. Although the current investment principle in Korea more or less reflects the primary purpose, the second aim is not fully reflected and might be too strict about measuring the balanced and sustainable influence on the regional economy. Considering that the house price is an output of regional production, this research tried to establish more proactive quantitative models explaining how ‘transport accessibility to infrastructure’ raises the apartment price in South Korea while interacting with the industries. This study achieved four main results according to the model. First, most urban infrastructures raise apartment prices per square meter about ten times higher than most industries, given a percentage change. Second, the synergy between industrial sales and infrastructural accessibility was negative in most cases, showing a limit of infrastructural investment alone to facilitate sustainable development. Third, an impoverished area tends to conclude positive synergies between industries and infrastructures, justifying more infrastructural investment in those poor areas. Finally, a public service behaves as infrastructure, which re-examines public services’ functionality of the prime water. Conclusively, this research proved that accessibility to core infrastructures is essential in conjunction with land use status resulting from industrial geography to rebalance Korean apartment prices for sustainable investment in transportation sectors.
Keywords: accessibility; house price; industry; transport investment